Implementation of time of flight polarized neutron imaging at IMAT-ISIS - U.K. Oji; V. Pacheco; M. Sahlberg; A. Backs; R. Woracek; D.E. Pooley; G.J. Nilsen; K. Nemkovski; W. Kockelmann; A.S. Tremsin; A. Hilger; R. Ziesche; et al. (Materials & Design, 2023)
In this study, we report the first case of design and implementation of a polarized neutron imaging option on the Imaging and Materials Science & Engineering Station (IMAT). This is a significant addition to the capabilities of the station that allows the characterization of advanced magnetic materials for different engineering applications. Combining its time-of-flight feature with a polarized beam yields data that facilitate both quantitative and qualitative analysis of magnetic materials. Using the simple field of an aluminium solenoid, we perform a characterization of the new setup. In addition, we present polarized measurements of additively manufactured (AM) MnAl samples where the magnetic anisotropy due to the fabrication process has been investigated as a first scientific application of the setup. The results indicate that the anisotropy of the material can be engineered through variation of the AM fabrication parameters.